BAITUL MAAL WAT TAMWIL DIPANDANG DARI SUDUT AGAMA, SERTA SEJARAH BERDIRINYA DI INDONESIA - Tuty Sariwulan (Jurnal Ilmiah Econosains, 2012)
Abstract Islamic banking hasn’t been able to touch the micro and small enterprises (MSEs) from street vendors to merchants in the traditional market which is usually referred as the grassroots economy. Driven by a sense of deep concern to many poor people are trapped by moneylenders and also in order to provide an alternative for those to expand its business but can’t be directly to related Islamic banking ( BMI and BPRS ) because the business it’s relatively small and micro, then in 1992 a small financial institutions that operate and use a combination of concepts Baitul Maal and Baitul Tamwil as the target and the scale on the micro business sector. The institutions "ventured" named Baitul Maal Wat Tamwil abbreviated BMT.